Neuroprotective effect of an unsaturated mannuronate oligosaccharide derived from enzyme-degraded polymannuronate on an in vitro Parkinson's disease-like model - Decheng Bi; Jinfeng Huang; Nanting Zhu; Jue Cao; Yan Wu; Lijun Yao; Xueying Ding; Jianyong Wu; Xu Cao; Xu Xu (Journal of Agriculture and Food Research)
This study mainly aimed to explore the intervention effect of an unsaturated mannuronate oligosaccharide (MOS) on Parkinson's disease (PD) and its potential mechanism at the cellular level. MOS, which possesses high water solubility and excellent biocompatibility, was prepared by enzyme degradation of alginate-derived polymannuronate. In 6-hydroxydopamine (6-OHDA)-induced SH-SY5Y cell culture, MOS treatment effectively augmented the expression of tyrosine hydroxylase (TH), PTEN-induced putative kinase 1 (PINK1) and parkin but suppressed the expression of α-synuclein (α-syn). Moreover, MOS exerted antioxidant activity by suppressing the excessive generation of reactive oxygen species and enhancing the activity of superoxide dismutase. MOS also inhibited 6-OHDA-induced apoptosis by enhancing mitochondrial membrane potential and mitigating the Bax/Bcl-2 pathway and improving autophagy that was blocked by 6-OHDA. In summary, these results have demonstrated the significant neuroprotective effect of MOS on SH-SY5Y cells, indicating that MOS has a certain intervention effect on the development of PD. This provides a promising foundation for developing novel therapeutic strategies targeting neurodegenerative disorders.